Analisis Pendapatan Usahatani Cabai Rawit Di Desa Kombi Kecamatan Kombi Kabupaten Minahasa - Rawung, Michelle Lovely; Rumagit, Grace Adonia Josephia; Pangemanan, Paulus Adrian (Sam Ratulangi University, 2024)
The purpose of this study was to analyze the income of cayenne pepper farming in Kombi Village, Kombi District, Minahasa Regency. The research was conducted from July to August 2023. This research was conducted in Kombi Village, Kombi District, Minahasa Regency. The data collection method used is by collecting primary and secondary data. Primary data was obtained through direct interviews with cayenne pepper farmers in Kombi Village, Kombi District, Minahasa Regency using questions that had been prepared in the form of a questionnaire. Secondary data were obtained from data from the agriculture office and other sources related to the research. The sampling method used in the study was probability sampling technique, namely sampling that provides equal opportunities for each member of the population to be selected as a sample member. Researchers took a sample of 8 cayenne pepper farmers who already had production results in Kombi Village, Kombi District, Minahasa Regency. Data analysis used descriptive quantitative analysis in determining production costs, revenue, income, and R / C ratio. The results showed that cayenne pepper farming in Kombi Village, Kombi District, Minahasa Regency obtained an income of IDR56.347.923 per farmer per one planting season, and income per hectare was obtained at IDR150.187.532, and the results of the R / C Ratio analysis obtained 4,21 which means it is feasible to cultivate.